Digital Transformation from a Regulatory Perspective (GESTIÓN Y TENDENCIAS, 2020)
Digital preservation is a set of tasks, techniques, methods, and technologies that seek to guarantee access to information in digital format. This article offers an approach to the key concepts related to digital preservation, the benefits of its implementation, the main associated technological aspects, the challenges, and a look at the current state of digital preservation in Chile.